An optimized quantitative proteomics method establishes the cell type‐resolved mouse brain secretome. (21st September 2020) - Tüshaus, Johanna; Müller, Stephan A; Kataka, Evans Sioma; Zaucha, Jan; Sebastian Monasor, Laura; Su, Minhui; Güner, Gökhan; Jocher, Georg; Tahirovic, Sabina; Frishman, Dmitrij; Simons, Mikael; Lichtenthaler, Stefan F
Abstract: To understand how cells communicate in the nervous system, it is essential to define their secretome, which is challenging for primary cells because of large cell numbers being required. Here, we miniaturized secretome analysis by developing the "high‐performance secretome protein enrichment with click sugars" (hiSPECS) method. To demonstrate its broad utility, hiSPECS was used to identify the secretory response of brain slices upon LPS‐induced neuroinflammation and to establish the cell type‐resolved mouse brain secretome resource using primary astrocytes, microglia, neurons, and oligodendrocytes. This resource allowed mapping the cellular origin of CSF proteins and revealed that an unexpectedly high number of secreted proteins in vitro and in vivo are proteolytically cleaved membrane protein ectodomains. Two examples are neuronally secreted ADAM22 and CD200, which we identified as substrates of the Alzheimer‐linked protease BACE1. hiSPECS and the brain secretome resource can be widely exploited to systematically study protein secretion and brain function and to identify cell type‐specific biomarkers for CNS diseases. Synopsis: The proteomic hiSPECS method miniaturizes secretome analysis and establishes the cell type‐resolved mouse brain secretome resource. This enabled the mapping of the cellular origin of proteins in CSF and secreted from brain slices under neuroinflammatory conditions. hiSPECS miniaturizes secretome analysis in the presence of serum proteins. The cell‐type resolved secretome resource includes the secretome of primary astrocytes, microglia, oligodendrocytes and cortical versus hippocampal neurons. Proteolytic shedding of membrane proteins is a major mechanism for protein secretion. The resource allows mapping the cellular origin of proteins in CSF and secreted from brain slices upon LPS stimulation. hiSPECS identifies CD200 and ADAM22 as new substrates of the Alzheimer‐linked protease BACE1. Abstract : hiSPECS, a miniaturized proteomics protocol based on pull‐down of glycosylated secretory proteins from smaller numbers of cells, defines the specific secretomes of astrocytes, microglia, neurons and oligodendrocytes from primary cells, as well as secretion changes in LPS‐induced inflammatory conditions.